Removal of Boundary Markers on Sebatik Island: Legal Implications for Regional Sovereignty and Protection of Border Communities - Titaley, Gracio Sulistyo; Wattimena, Josina Augustina Yvonne; Leatemia, Wilshen (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Borders represent a manifestation of state sovereignty. The relocation of boundary markers between Indonesia and Malaysia on Sebatik Island without formal agreement violates international law. Such actions may alter legally recognized territorial boundaries and thus constitute a breach of sovereignty, potentially leading to serious legal implications.Purposes of the Research: The purpose of this study is to analyze the legal consequences of relocating boundary markers between nations, particularly between Indonesia and Malaysia on Sebatik Island. It also examines the implications for territorial sovereignty, bilateral relations, and the provisions of international law governing officially recognized and binding state borders.Methods of the Research: This research is a normative legal research “legal research" is a study of documents (using legal material sources such as laws and regulations, court decisions, legal theories and or opinions of scholars). In simple terms, this type of research is also called doctrinal legal research, literature or document studies.Findings of the Research: The study found that unilateral stake removals not only violate international law, but also threaten the economic and social rights of border communities, as well as weaken Indonesia's bargaining position in bilateral negotiations. In addition, weak surveillance in the border area also allows for unilateral transfers by interested parties.